2021
DOI: 10.1016/j.abrep.2021.100391
|View full text |Cite
|
Sign up to set email alerts
|

Is the proposed distinction of gaming disorder into a predominantly online vs. offline form meaningful? Empirical evidence from a large German speaking gamer sample

Abstract: Highlights Disordered gaming is distinguished by predominantly online, offline, and unspecific gaming. Online gamers showed the highest tendencies towards disordered gaming. Gaming via desktop computers was linked with the highest disordered gaming levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…To be officially diagnosed with gaming disorder (“digital gaming” or “video gaming”), a patient must exhibit three symptoms: impaired control over gaming, increasing priority given to gaming over other activities to the extent that gaming takes precedence over other interests and daily activities, and continuation or escalation of gaming despite the occurrence of negative consequences [ 24 ]. The WHO’s distinction between online and offline gaming modes is significant because online gamers have the highest disordered gaming scores, followed by mixed gamers (those who say they prefer both online and offline gaming), and offline gamers [ 35 ]. In comparison to the DSM-5 IGD diagnosis criteria, the ICD-11 diagnosis criteria emphasize functional impairment [ 36 ].…”
Section: What Is An Addiction?mentioning
confidence: 99%
“…To be officially diagnosed with gaming disorder (“digital gaming” or “video gaming”), a patient must exhibit three symptoms: impaired control over gaming, increasing priority given to gaming over other activities to the extent that gaming takes precedence over other interests and daily activities, and continuation or escalation of gaming despite the occurrence of negative consequences [ 24 ]. The WHO’s distinction between online and offline gaming modes is significant because online gamers have the highest disordered gaming scores, followed by mixed gamers (those who say they prefer both online and offline gaming), and offline gamers [ 35 ]. In comparison to the DSM-5 IGD diagnosis criteria, the ICD-11 diagnosis criteria emphasize functional impairment [ 36 ].…”
Section: What Is An Addiction?mentioning
confidence: 99%
“…Taking into account the increasing number of studies reporting the potential addictive effects of video games (Montag et al, 2019a , 2021a ; Pontes, 2018 ; Stevens et al, 2021 ), before the official GD criteria proposed by the World Health Organization (WHO), the American Psychiatric Association (APA) introduced ‘Internet Gaming Disorder’ (IGD) in the fifth revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; APA, 2013 ) in 2013. Within the DSM-5, IGD was included under Section III as a ‘Condition for Further Study’ as further research on this issue was required as pointed out (APA, 2013 ).…”
Section: Disordered Gaming Frameworkmentioning
confidence: 99%
“…Technology use and devices help boosting users' communication levels, social group connections, self-reported life satisfaction and wellbeing levels [1][2][3]. Despite such positive outcomes, previous studies reported that excessive technology use may lead to detrimental outcomes, with adolescents being considered to be more susceptible to harmful digital technology use [4], particularly in relation to Problematic Internet Use (PIU) [5,6], with electronic gaming also being a highly popular activity among adolescents due to the latest technological advancements, enticing graphics with realistic images and complex gaming systems [7,8].…”
Section: Introductionmentioning
confidence: 99%